High-speed rail transport valuation - Pimentel, Pedro Miguel (2022)
In this paper, the optimal timing for investing in high-speed rail projects under uncertainty in relation to the utility provided to railway users was investigated. To accomplish this, a continuous time real options analysis framework using a stochastic demand model was developed to determine the optimal time to invest. Uncertainty upon investment expenditures was also added in an extended framework. The value of the option to defer and the investment opportunity value were also assessed